Magnificent Xinjiang - Xiao, Bian ("Charming Xinjiang" series, 2014)
Magnificent Xinjiang introduces a wide variety of natural landscapes in Xinjiang. Firstly it unfolds before readers the general characteristics of terrain and weather in Xinjiang; secondly it depicts its majestic mountains and canyons, elegant lakes, surging rivers, extensive grasslands, vast deserts, unyielding desert poplars and the fantastic Demon Town. Through vivid descriptions, readers can not only see the diverse scenery but also learn the harmonious development between human and nature.